PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN DI INDUSTRI PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA DENGAN COMPETITIVE ADVANTAGE SEBAGAI VARIABEL INTERVENING - Euis Nurhayati; Bustanul Arifin; Windu Mulyasari (Tirtayasa Ekonomika, 2019)
This study aims to empirically examine the effect of intellectual capital on the performance of firm and competitive advantage as a mediating variable. Firm performance used in this study measured using Return On Asset (ROA), and Return On Equity (ROE). While intellectual capital is measured by using VAIC™ method developed by Pulic (1998 ). Competitive advantage is measured by cost of R&D.This study used a sample of banking companies listed on the Stock Exchange period 2012-2015 using purposive sampling method . The data used were obtained from the annual financial statements of banking companies listed on the Stock Exchange. The method of analysis used in this study is multiple regression analysis . This method was chosen because all of the data is matrix variable. The results of this study indicate that VAIC has significant effect on ROA. ROA has a significant effect on competitive advantage, and competitive advantage has the effect of mediation on the VAIC and ROA.Keywords:Intellectual Capital;Firm Size;Competitive Advantage;FirmPerformance;Banking